Comparative Study of Protective Effect of Cimetidine and Verapamil on Paracetamol-Induced Hepatotoxicity in Mice - Lubna Danish; Riffat Siddiq; Sarwat Jahan; Mehwish Taneez; Manzoor Khan; Marva Sandhu (International Journal of Hepatology)
Paracetamol, chemically known as acetaminophen, if taken in higher doses has hepatotoxic potential. Cimetidine by inhibiting the cytochromal enzymes and reducing the production of the toxic metabolite can reduce the hepatotoxic potential while Verapamil can act as a hepatoprotective by maintaining calcium homeostasis. The present study was conducted to study the hepatoprotective activity of Cimetidine and Verapamil against the toxicity induced by paracetamol. In addition to the group receiving only distilled water or 300 mg/kg paracetamol additional groups were added treated with 150 mg/kg Cimetidine and Verapamil alone or both. The Liver function tests and histopathology revealed hepatotoxicity in the group receiving paracetamol (PCM) while normal parameters were observed in the groups receiving Cimetidine and Verapamil. Our results strongly suggested that Cimetidine and Verapamil possess hepatoprotective potential against paracetamol induced hepatotoxicity.